Outlook Indikator Makro Global dan Sektor Pertanian 2016-2019 - Muhammad Maulana; Pantjar Simatupang; Reni Kustiari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
Macroeconomic policies are important to consider in determining agricultural targets and policies. Thus, it is necessary to conduct an analysis of historical circumstances, current status, trends, and prospects of agricultural macro indicators. This study aims to forecast and to analyze the main macroeconomic indicators in the agricultural sector from 2016 to 2019. The study used secondary data and information. Projection was calculated using two alternative models, i.e. economic behavior and polynomial trend regression models. The results showed that after a slowdown in 2011-2014, Indonesia's economy rebounded in 2015-2016. GDP growth was expected 5,6 to 5,8% while inflation was 6,8 to 7,9% in 2016-2019. Agricultural GDP’s growth in 2016-2019 was estimated around 3,5-3,7%/year. Agricultural exports and imports were expected to increase to 10%/year and 12%/year for the period of 2016-2019, respectively. Agriculture will become the economic anchor through increases in food production and industrial commodities, as well as managing generating-inflation commodities’ prices. AbstrakKebijakan makroekonomi penting dipertimbangkan dalam menentukan target dan kebijakan sektor pertanian sehingga diperlukan suatu analisis mengenai keadaan historis, status terkini, kecenderungan yang terjadi, dan prospek indikator makro sektor pertanian. Kajian ini bertujuan untuk memproyeksi dan menganalisis indikator makro utama sektor pertanian tahun 2015-2019. Kajian ini menggunakan data dan informasi sekunder. Perhitungan proyeksi menggunakan dua alternatif yaitu melakukan estimasi dengan model perilaku ekonomi atau dengan model regresi tren polinomial. Hasil kajian menunjukkan bahwa setelah perlambatan pada 2011-2014, perekonomian Indonesia rebound pada 2015/2016. Pertumbuhan PDB diperkirakan pada kisaran 5,6-5,8% sementara inflasi umum berada pada kisaran 6,8-7,9% pada 2016-2019. Laju pertumbuhan PDB sektor pertanian pada 2016-2019 diperkirakan dalam kisaran 3,5-3,7%/tahun. Ekspor pertanian diperkirakan meningkat 10%/tahun pada 2016-2019. Impor pertanian akan meningkat 12%/tahun pada 2016-2019. Sektor pertanian akan menjadi jangkar perekonomian melalui peningkatan produksi pangan dan komoditas industri serta mengelola harga komoditas pemicu inflasi.